A temporal study of the effects of online opinions : information sources matter - Huang, Jianxiong (2020)
This study examines when and why online comments from different sources and platforms influence a movie’s box office receipts over time. Premised on the theory of information search, we hypothesize that consumers are more likely to engage in active search in the early stages of a movie’s release due to greater choice uncertainty, and passive attention is more likely to kick in for later stages of a movie’s release, as uncertainty decreases. To test the proposed hypotheses, we tracked over 1,500 sources of online expert and consumer reviews for cinematic movies released for an entire year and continuously monitored major social media sites (e.g., Twitter) for comments. We text-mined the comments to elucidate the sentiments and analyzed the data. Confirming our hypotheses, the results showed that expert reviews and pull-based peer comments have a significant influence in early stages of a movie’s release, and the effects decrease over time. In contrast, the volume of comments from push-based microblog platforms have a significant influence on later box office receipts. Our research demonstrates that online opinions are not always persuasive and useful, and our findings provide insights into when consumers are likely to pay attention to which types of online opinions.